O assessoramento técnico-pedagógico dos coordenadores de cursos da EPTNM no CETAM: percursos pedagógicos em busca da educação omnilateral no contexto amazonense - Souza, Pedro Santarém de (2022)
The study arose from inquiries regarding the analysis of the pedagogical praxis of the Coordinator of Technical Courses at the Technical Training Coordination (Fortec) within the institutional scope of the The study arose from inquiries about the analysis of the pedagogical praxis of the Coordinator of Technical Courses at the Technical Training Coordination (Fortec) at the Technological Education Center of Amazonas (Cetam), in relation to the effectiveness of EPTNM in the interior of the state. The research is centered on Line 02 of the Professional Master's Degree in Professional and Technological Education - "Organization and Memories of Pedagogical Spaces in EPT", linked to macroproject 06 - "Organization of pedagogical spaces in EPT". The research problem was: when analyzing the pedagogical praxis of Fortec/Cetam course coordinators, what are the points of approximation and/or distance from the concept of omnilateral training in EPT? The general objective was to investigate the pedagogical praxis of the coordinators of Fortec/Cetam in the process of technical-pedagogical advice to teachers, highlighting the points of approximation or distance from the EPT conception in the omnilateral perspective; and the specific objectives were: to investigate the EPT concepts present in the actions of the coordinators in the technical-pedagogical advisory process, aiming at improving the teaching and learning process; analyze the main pedagogical activities of the coordinators of Fortec/Cetam courses in terms of work as an educational principle and the integration between the scientific, technological and cultural dimensions; to propose an organization of educational actions to assist course coordinators in monitoring teaching practices focused on the curriculum, teaching planning, learning assessment and teaching methodologies of Fortec/Cetam teachers. The sample universe of the research comprised 10 (ten) participants: 02 (three) pedagogues and 08 (eight) course coordinators (bachelors) in the sector. It is an action research and the collection instruments used were: participant observation, questionnaire and focus group. The speeches were transcribed and submitted to content analysis: pre-analysis, exploration of the material and treatment of the results in Bardin (1977). We used the theoretical basis referring to the assumptions of Saviani (2007), Marx (1998), Manacorda (1990), Borges (2007), among others. The results demonstrate that the Fortec/Cetam course coordinator presents himself as an important professional for the improvement of the teaching and learning process, since his activities include organizational actions, means and goals, with pedagogical work being the essence of your praxis. In view of this, as these are real contexts, some limiting conditions for their work are presented. It is also highlighted the training needs of the group on the conceptual bases of EPT. As a result of the research, an educational product was built in the format of "Pedagogical Plan for Course Coordinator: Educational Praxis in Professional and Technological Education", with the purpose of reflecting on alternatives for the realization of the EPTNM and assisting in the technical-pedagogical advising of courses, focusing on coordinators and similar professionals.